Medicalization of Judicial Mode of Execution: A Critical Study in American Context (Medico Legal Update, 2020)
Modes of judicial execution of death sentence have to be determined in light of various objective factorslike prevailing atmosphere of the international opinion, international norms and standards, contemporarypenological theories and ever progressing standards of human decency. Though it’s essential to adapt themost civilized method of judicial execution, nevertheless, what is more important is how that civilizedprocess of execution is carried out. History is witness to the fact that how medical professionals have madeinvaluable contributions to make the existing modes of execution more civilized, humane and efficientby playing the most pivotal role. Medicalization of the process of judicial execution through intravenouslethal injection is not novel. However, currently direct participation of physicians in the implementationof the death penalty through intravenous lethal injection has become an extremely controversial subject,initiating voluminous intellectual debate at global platforms. Hence, an appropriate contouring of suchparticipation is increasingly coming under sharp scrutiny on ethical and legal grounds. The questionarises, will the physicians not be guilty of gross professional misconduct by refusing to oversee theexecutions and taking care of the condemned persons in their last crucial hours, thereby neglecting theirethical responsibility to minimize the suffering and maximize the comfort. Physicians need to fulfill theirrole as caregivers by actively participating in the implementation and development of lethal injection as themost humane mode of judicial execution.